Miniaturized Origami Robots: Actuation Approaches and Potential Applications. Issue 2 (9th November 2021) - Tang,, Junjie; Wei, Fanan
Abstract: Origami, a paper folding art, has inspired engineering applications in various fields for decades. It provides a simple approach to realize the transformation between simple 2D composite sheets and complex 3D functional structures. By integrating the origami concept with smart materials, a number of advanced origami robots have been developed with self‐deploying and programming capacities to respond to external environment stimuli. At present, miniaturized origami robots have demonstrated advantages in many‐profile applications, including bio‐inspired robotics, biomedical engineering, and environment monitoring. However, how to properly drive origami robots is a big challenge. In this paper, the investigation and analyses of the previous literature focus on the various actuations of miniaturized origami robots, including the magnetic, light, electric, swelling, motors, thermal, and other actuation methods. Finally, the article investigates applications of actuation methods for miniaturized origami robots with various functions, and discusses the challenges and opportunities in future applications. Abstract : Origami robots are a series of autonomous machines actuated by external environment. The self‐folding processes of origami robots are realized by interactions between actuation fields and intelligent responsive materials. Multifunctional miniaturized origami robots with high degrees of freedom and remote actuation are expected to realize significant applications in bio‐inspired robotics.